Nanoscale zero-valent iron for metal/metalloid removal from model hydraulic fracturing wastewater. (June 2017) - Sun, Yuqing; Lei, Cheng; Khan, Eakalak; Chen, Season S.; Tsang, Daniel C.W.; Ok, Yong Sik; Lin, Daohui; Feng, Yujie; Li, Xiang-dong
Abstract: Nanoscale zero-valent iron (nZVI) was tested for the removal of Cu(II), Zn(II), Cr(VI), and As(V) in model saline wastewaters from hydraulic fracturing. Increasing ionic strength ( I ) from 0.35 to 4.10 M (Day-1 to Day-90 wastewaters) increased Cu(II) removal (25.4–80.0%), inhibited Zn(II) removal (58.7–42.9%), slightly increased and then reduced Cr(VI) removal (65.7–44.1%), and almost unaffected As(V) removal (66.7–75.1%) by 8-h reaction with nZVI at 1–2 g L −1 . The removal kinetics conformed to pseudo-second-order model, and increasing I decreased the surface area-normalized rate coefficient ( k sa ) of Cu(II) and Cr(VI), probably because agglomeration of nZVI in saline wastewaters restricted diffusion of metal(loid)s to active surface sites. Increasing I induced severe Fe dissolution from 0.37 to 0.77% in DIW to 4.87–13.0% in Day-90 wastewater; and Fe dissolution showed a significant positive correlation with Cu(II) removal. With surface stabilization by alginate and polyvinyl alcohol, the performance of entrapped nZVI in Day-90 wastewater was improved for Zn(II) and Cr(VI), and Fe dissolution was restrained (3.20–7.36%). The X-ray spectroscopic analysis and chemical speciation modelling demonstrated that the difference in removal trends from Day-1 to Day-90 wastewaters was attributed to: (i) distinctive removal mechanisms of Cu(II) and Cr(VI) (adsorption, (co-)precipitation, and reduction), compared to Zn(II) (adsorption) and As(V) (bidentate inner-sphere complexation); and (ii) changes in solution speciation (e.g., from Zn 2+ to ZnCl3 − and ZnCl4 2− ; from CrO4 2− to CaCrO4 complex). Bare nZVI was susceptible to variations in wastewater chemistry while entrapped nZVI was more stable and environmentally benign, which could be used to remove metals/metalloids before subsequent treatment for reuse/disposal. Graphical abstract: Highlights: nZVI could remove Cu(II), Zn(II), Cr(VI), and As(V) from fracturing wastewaters. High salinity enhanced Fe dissolution and reduced removal rates except Cu(II). nZVI entrapment mitigated Fe dissolution and improved metal(loid) removal. Removal efficiency varied with interaction mechanisms and solution speciation.